International legal regulation of the company’s creation in the USA - ILCHENKO, Ганна (Ius Modernum, 2019)
Background. Given the de-offshorization processes around the world, one of the most important issues for beneficiaries is the right choice of jurisdiction. Therefore, for those who have decided to register a legal entity or other type of business entity not in Ukraine, many things must be taken into account in order for its business to operate in the legal field. Given the reform of the tax system of the US, the issue of registration and operation of companies in the United States has become relevant. Analysis of recent research and publications. The works of Zhornokuy Yu., Samus A., Shimon S., Semilitina N., Sukhanov E.and others are devoted to the problems of the creation and operation of legal entities in the Anglo-Saxon family of law, in particular the United States. The aim of the article is a comprehensive analysis of the legal regulation of the main stages that must be passed by anyone who decides to register their business in the United States of America in accordance with US law. Materials and methods. Methodological basis is a number of methods: philosophicalmethods of cognition (for example, dialectic), general scientific methods (analysis and synthesis, modeling, abstraction) and special methods used in the interpretation of the rules of law, comparative legal analysis were used. Results.Before setting up a company in the United States, its founder must answer for a number of questions, namely: why does he generally have business in America, which state to choose, which legal form to choose, which tax aspects to consider, how not to disclose information about as a business owner, which documents need for registration, how much time and money is required, how to protect yourself from legal risks, how to protect your brand, which visa is better to get, etc. The corporation (Corp / Inc) and the limited liability company (LLC) are the mostpopular in the US because these forms, unlike the partnership and the private entrepreneur, do not provide full ownership of the founder. Terms and cost of company registration depends on the state and company form.By registering your company, you first need to get a Federal Tax Identification Number in the Internal Revenue Service (IRS) Conclusion. Summarizing the foregoing, it should be emphasized that US law does not contain clear indications of who should register the company, but the state authorities that make the registration and issue the relevant certificates recommend that a lawyer be involved. Firstly, a lawyer in the United States must have a license that grantsthe right to practice in the United States. It helps to prepare, analyze and submit all necessarydocuments. Ukrainian lawyers are offering US law services without a license, which residents of Ukraine, as a rule, do not know. This practice is unlawful, since only lawyers licensed in the United States are eligible to provide legal services in the United States.